Elevated Blood Lead Levels in Infants and Children in Haiti, 2015. (January 2019) - Carpenter, Chris; Potts, Brittany; von Oettingen, Julia; Bonnell, Ric; Sainvil, Michele; Lorgeat, Viviane; Mascary, Mie Christine; She, Xinshu; Jean-Baptiste, Eddy; Palfrey, Sean; Woolf, Alan D.; Palfrey, Judith
Objective: Few studies have reported blood lead levels (BLLs) in Haitian children, despite the known presence of lead from environmental factors such as soil, water, leaded paint and gasoline, improperly discarded batteries, and earthquakes. We sought to determine the prevalence of elevated blood lead levels (EBLLs) among healthy Haitian children. Methods: We enrolled children aged 9 months to 6 years from 3 geographic areas in Haiti (coastal, urban, and mountain) from March 1 through June 30, 2015. We obtained anthropometric measurements, household income, potential sources of lead exposure, and fingerstick BLLs from 273 children at 6 churches in Haiti. We considered a BLL ≥5 μg/dL to be elevated. Results: Of 273 children enrolled in the study, 95 were from the coastal area, 78 from the urban area, and 100 from the mountain area. The median BLL was 5.8 μg/dL, with higher levels in the mountain area than in the other areas ( P < .001). BLLs were elevated in 180 (65.9%) children. The prevalence of EBLL was significantly higher in the mountain area (82 of 100, 82.0%; P < .001) than in the urban area (42 of 78, 53.8%) and the coastal area (56 of 95, 58.9%; P < .001). Twenty-eight (10.3%) children had EBLLs ≥10 μg/dL and 3 (1.1%) children had EBLLs ≥20 μg/dL. Exposure to improperly discarded batteries ( P = .006) and living in the mountain area ( P < .001) were significant risk factors for EBLLs. Conclusions: More than half of Haitian children in our study had EBLLs. Public health interventions are warranted to protect children in Haiti against lead poisoning.